THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND WORK ENVIRONMENT ON NURSES’ PERFORMANCE - M Ahmed; Kosasih (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the influence of transformational leadership and work environment on nurses’ performance at Hospital X. The research employs a quantitative approach with a cross-sectional design and involves 30 nurses as respondents. Data were collected using structured questionnaires and analyzed using multiple linear regression, after conducting validity, reliability, normality, multicollinearity, and heteroskedasticity tests to ensure the quality of the data. The results show that transformational leadership and work environment both have a positive and significant effect on nurses’ performance, both partially and simultaneously. The regression analysis indicates that transformational leadership has a stronger effect compared to the work environment, while the coefficient of determination (R²) shows that 57.9% of the variation in nurses’ performance is explained by these two variables. The study concludes that effective transformational leadership and a supportive work environment are critical factors in enhancing nurses’ performance, which in turn contributes to improved healthcare service quality.